2015
DOI: 10.1038/srep07910
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically porous silicon–carbon–nitrogen hybrid materials towards highly efficient and selective adsorption of organic dyes

Abstract: The hierarchically macro/micro-porous silicon–carbon–nitrogen (Si–C–N) hybrid material was presented with novel functionalities of totally selective and highly efficient adsorption for organic dyes. The hybrid material was conveniently generated by the pyrolysis of commercial polysilazane precursors using polydivinylbenzene microspheres as sacrificial templates. Owing to the Van der Waals force between sp2-hybridized carbon domains and triphenyl structure of dyes, and electrostatic interaction between dyes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(95 citation statements)
references
References 74 publications
3
92
0
Order By: Relevance
“…The adsorption of MG by HNTs obeyed pseudo-secondorder kinetics with activation energy 18.28 kJ/mol, 49. Hierarchically macro/microporous silicon-carbonnitrogen (Si-C-N) hybrid material ------- (Meng et al 2015) suggested that the process was physisorption. The best-fit adsorption isotherm was achieved with the Langmuir model, indicating that homogeneous adsorption occurred.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…The adsorption of MG by HNTs obeyed pseudo-secondorder kinetics with activation energy 18.28 kJ/mol, 49. Hierarchically macro/microporous silicon-carbonnitrogen (Si-C-N) hybrid material ------- (Meng et al 2015) suggested that the process was physisorption. The best-fit adsorption isotherm was achieved with the Langmuir model, indicating that homogeneous adsorption occurred.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…The Langmuir isotherm model is based on the assumption that the adsorption process is a monolayer adsorption on a homogeneous adsorbent surface, there is no interaction between adsorbed molecules and the binding sites are nite and have the identical sorption energies. 40 The equation of Langmuir isotherm could be expressed as follows.…”
Section: Adsorption Isotherms Study Of Mb Onto Ylc-ac-3mentioning
confidence: 99%
“…Meanwhile, the presence of macropores and interconnected mesopores enables the fast diffusion of molecules into the internal pores (especially for large molecules), which greatly improves the adsorption rate. [33][34][35] However, the tedious preparation procedures for the hierarchically porous adsorbents greatly hinder their practical applications. Furthermore, there are still some inaccessible binding sites in such materials, leading to binding efficiencies far below 100% (relative to the molar amount of the functional groups).…”
Section: Introductionmentioning
confidence: 99%